Carbon-based electrode of flow battery as well as preparation method and application of carbon-based electrode

By etching and doping carbon-based electrodes with nitrogen, the method addresses the limitations of existing electrodes, enhancing their electrochemical performance and scalability for vanadium redox flow batteries.

CN120319833AActive Publication Date: 2025-07-15HUNAN AGRI UNIV

Patent Information

Application Number
CN202510788649.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-13
Publication Date
2025-07-15
Estimated Expiration
2045-06-13

AI Technical Summary

Technical Problem

The existing all-vanadium flow battery electrode materials have problems such as scarce active sites, low catalytic activity and structural-function imbalance. The existing modification technology is difficult to improve efficiently in terms of cost and performance.

Method used

By in-situ etching and doping the carbon-based material under high temperature conditions, a porous carbon fiber surface doped with nitrogen is formed, the electrode-electrolyte contact area is increased, and the electrocatalytic activity of the electrochemically active site is enhanced.

Benefits of technology

It realizes high activity, strong durability and low cost of electrode materials, is suitable for industrial production, and improves the voltage and energy efficiency of the flow battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120319833A_ABST
    Figure CN120319833A_ABST
Patent Text Reader

Abstract

The invention relates to a flow battery carbon-based electrode and a preparation method and application thereof, and the preparation method comprises the following steps: respectively dissolving cobalt salt and alkali in a polar organic solvent, and uniformly mixing to form a precursor solution; placing a carbon-based material in the precursor solution, and carrying out a hydrothermal reaction to obtain a carbon-based electrode precursor; and performing high-temperature carbonization on the carbon-based electrode precursor in an inert atmosphere, cooling to room temperature after the reaction is completed, and then cleaning and removing impurities from a product to obtain the carbon-based electrode, the polar organic solvent is at least one of formamide, acetonitrile and N, N-dimethylformamide; after cobalt cyanide is deposited on the surface of the carbon-based material, surface etching and nitrogen doping are carried out on the carbon-based material under the high-temperature condition, surface modification of the carbon-based material is achieved, the contact area of the surface of the carbon-based electrode and electrolyte is increased, and the electrochemical performance of the carbon-based electrode is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of flow battery electrode materials, and more specifically, to a carbon-based electrode for a flow battery, a preparation method thereof, and an application thereof. Background Art

[0002] Under the background of the global energy structure transformation, the development of efficient energy storage technologies has become the key to solving the intermittency problems of renewable energies (such as solar energy and wind energy). Flow batteries are regarded as an optimal solution for large-scale energy storage systems due to their advantages such as power-capacity decoupling design, long cycle life, and high safety. Among them, the all-vanadium flow battery (VRFB) has achieved commercial demonstration applications after more than forty years of development, but its energy conversion efficiency and cycle stability are still restricted by the performance bottleneck of electrode materials.

[0003] As the mainstream electrode of the all-vanadium flow battery (VRFB), carbon-based materials (such as graphite felt, carbon cloth, etc.) have three inherent defects despite their advantages such as low cost and excellent chemical stability: scarce active sites (insufficient effective specific surface area, resulting in slow reaction kinetics), low intrinsic activity (lack of catalytic active centers, high charge transfer impedance), and structural-functional imbalance (traditional modification methods often sacrifice mechanical strength to improve activity). Existing electrode modification technologies have significant limitations: although the thermal activation method can introduce oxygen-containing functional groups, the increase in the density of active sites is limited; the strong acid oxidation method will severely erode the crystal lattice structure of carbon fibers, resulting in a decrease in tensile strength and affecting the mechanical properties of the electrode; although noble metal modification can improve catalytic activity, it has high costs and problems of metal dissolution and pollution; plasma treatment relies on special equipment and has a low treatment rate, making it difficult to achieve large-scale production. These limitations severely restrict the wide application and performance improvement of electrode modification technologies in all-vanadium flow batteries.

[0004] Therefore, the development of electrode modification technologies with high activity, strong durability, and low cost has become the core topic for breaking through the industrialization bottleneck of all-vanadium flow batteries. Summary of the Invention

[0005] Based on the above technical problems existing in the prior art, the present invention provides a preparation method for a carbon-based electrode of a flow battery. By in-situ etching and doping of a carbon-based material under high-temperature conditions, a surface of porous carbon fiber doped with nitrogen elements can be formed on the carbon-based material, which can effectively increase the contact area between the electrode and the electrolyte, promote the full diffusion of electrons and ions at the interface. At the same time, the porous defects and nitrogen element doping contribute to enhancing the electrocatalytic activity of electrochemically active sites, so that the obtained carbon-based electrode exhibits excellent electrochemical performance.

[0006] To achieve the above object, the technical solution of the present invention is as follows: A preparation method for a carbon-based electrode of a flow battery, comprising the following steps: S1. Dissolve cobalt salt and alkali in polar organic solvents respectively, and mix them evenly to form a precursor solution; S2. Place the carbon-based material in the precursor solution and carry out a hydrothermal reaction to obtain a carbon-based electrode precursor; S3. Carry out high-temperature carbonization of the carbon-based electrode precursor under an inert gas atmosphere. After the reaction is completed, cool it to room temperature, and then wash and remove impurities from the product to obtain the carbon-based electrode; Among them, the polar organic solvent is at least one of formamide, dimethyl sulfoxide, acetonitrile, N,N-dimethylformamide, and ethanol.

[0007] In some embodiments, in step S2, the temperature of the hydrothermal reaction is 80 - 200 °C.

[0008] In some embodiments, in step S2, the time of the hydrothermal reaction is 8 - 15 h.

[0009] In some embodiments, in step S3, the carbonization temperature is 400 - 1200 °C.

[0010] In some embodiments, in step S3, the time of the carbonization reaction is 1 - 24 h.

[0011] In some embodiments, in step S3, the heating rate is 1 - 10 °C / min.

[0012] In some embodiments, the cobalt salt is at least one of cobalt nitrate, cobalt chloride, cobalt acetate, and cobalt sulfate.

[0013] In some embodiments, the alkali is at least one of sodium hydroxide and potassium hydroxide.

[0014] In some embodiments, the carbon-based material includes at least one of graphite felt, carbon cloth, and carbon paper.

[0015] In some embodiments, the mass ratio of the carbon-based material to the mass of the cyanide generated in the precursor solution is 1~100:1~100.

[0016] In some embodiments, in step S1, in the precursor solution, the molar concentrations of the cobalt salt and the alkali are respectively 0.01 - 0.1 mol / L.

[0017] In some embodiments, in step S3, the method of washing and removing impurities is to carry out treatment by pickling and / or water washing; the pickling treatment uses at least one of dilute sulfuric acid, hydrochloric acid, or nitric acid, and the acid concentration is 0.5 - 3.0 mol / L.

[0018] In some embodiments, in step S3, the pickling treatment method is as follows: The carbon-based electrode obtained after sintering is immersed in an acid solution for 6 - 20 h.

[0019] In some embodiments, the inert gas is one of argon, nitrogen, and helium; the gas flow rate is 50 - 200 mL / min.

[0020] The present invention also provides a carbon-based electrode obtained by the preparation method of any of the above embodiments. The surface of the carbon-based electrode has a micron-nano hierarchical porous structure.

[0021] In some embodiments, the porosity of the carbon-based electrode is 5.5 - 7.0 mL / g, and the specific surface area is 0.2 - 0.45 m 2 / g.

[0022] The present invention also provides a flow battery, which includes the above carbon-based electrode.

[0023] Compared with the prior art, the beneficial effects of the present invention are as follows: In the solution of the present invention, under hydrothermal conditions, cobalt salt, alkali, and a specific nitrogen-containing organic solvent react to deposit cobalt cyanide on the surface of the carbon-based material. Then, under high-temperature sintering conditions, cobalt cyanide reacts with the carbon-based material to undergo etching and doping reactions, etching the surface of the carbon-based material and doping nitrogen, while generating cobalt carbide, CO, and N2. Finally, the generated cobalt carbide, CO, and N2 substances are removed by washing and impurity removal, so that a nano-micron porous structure is formed on the surface of the carbon-based material, realizing etching and doping modification of the carbon-based material, forming a nitrogen-doped porous carbon electrode, which can effectively increase the contact area between the electrode and the electrolyte, promote the full diffusion of electrons and ions at the interface. At the same time, the porous defects and nitrogen element doping help to enhance the electrocatalytic activity of the electrochemically active sites.

[0024] The carbon-based material obtained by the method of the present invention is applied to a flow battery, which can make the flow battery have excellent voltage efficiency and energy efficiency.

[0025] The preparation method of the present invention has a simple process and low cost, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a scanning electron microscope image of the graphite felt electrode prepared in Example 1 and the blank graphite felt electrode before the etching reaction; among them, (a) is the scanning electron microscope image of the graphite felt without any treatment; (b) is the scanning electron microscope image of the graphite felt electrode prepared in Example 1. Figure 2 It is a cyclic voltammogram of the graphite felt electrode prepared in Example 1 and the blank graphite felt electrode before the etching reaction. Figure 3AC impedance diagram of the graphite felt electrode prepared in Example 1 and the blank graphite felt electrode before the etching reaction; Figure 4 Are the charge-discharge curves of the graphite felt electrode prepared in Example 1 and the blank graphite felt electrode before the etching reaction, respectively assembled into an all-vanadium redox flow battery. Detailed implementation manners

[0027] A lot of specific details are set forth in the following description in order to fully understand the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without departing from the connotation of the present invention. Therefore, the present invention is not limited by the specific implementations disclosed below.

[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the technical field to which this invention belongs. The terms used in the description of the present invention herein are for the purpose of describing specific embodiments only and are not intended to limit the present invention.

[0029] The experimental methods used in the following examples are all conventional methods unless otherwise specified; the reagents, materials, etc. used in the following examples can all be obtained from commercial sources unless otherwise specified. Example 1

[0030] A method for chemical etching and collaborative surface modification of a graphite felt electrode, comprising the following steps: S1. Dissolve 1.0 mmol of Co(NO3)2·6H2O and 1.0 mmol of KOH in 20 mL of formamide respectively to obtain solution A and solution B. After mixing, stir for 30 min until completely dissolved to obtain a mixed solution; S2. Transfer the mixed solution to a 100 mL high-pressure reaction kettle lined with polytetrafluoroethylene, put in four pieces of 2×2 cm 2 graphite felt, ultrasonically treat for 30 min, then seal the reaction kettle, and heat and react at 170 °C for 12 h; after the reaction is completed, cool to room temperature, collect the graphite felt, wash it with ethanol and dry it at 80 °C for 12 h to obtain a graphite felt electrode precursor; S3. Place the graphite felt electrode precursor in a tube furnace, heat it to 900 °C at a heating rate of 5 °C / min in an argon atmosphere and anneal for 2 h, cool it, wash it and dry it to obtain a composite electrode; S4. Immerse the composite electrode in a 3.0 mol / L H2SO4 solution for 6 h, wash it and dry it to obtain the final graphite felt electrode.

[0031] The prepared graphite felt electrode and the blank graphite felt electrode (graphite felt without any treatment) were subjected to SEM detection, and the results are as Figure 1As shown. As Figure 1 For the untreated graphite felt electrode, the surface of the carbon fiber is smooth without a porous structure. For the graphite felt electrode treated by the solution of this example, the surface of the carbon fiber has an obvious porous structure.

[0032] The graphite felt electrode prepared in Example 1 and a blank graphite felt electrode (graphite felt without any treatment) were respectively assembled into all-vanadium redox flow batteries for electrochemical performance tests. The test results are as Figures 2 - 4 shown. Among them: Figure 2 is the cyclic voltammogram of the graphite felt electrode with cobalt cyanide in-situ etching in Example 1 and the blank graphite felt electrode. This figure shows that the modified graphite felt electrode exhibits excellent positive and negative electrode catalytic performance.

[0033] Figure 3 is the AC impedance diagram of the graphite felt electrode with cobalt cyanide in-situ etching in Example 1 and the blank graphite felt electrode. This figure shows that the modified graphite felt electrode has a smaller charge transfer impedance.

[0034] Figure 4 is the charge-discharge curve of the graphite felt electrode with cobalt cyanide in-situ etching in Example 1 and the blank graphite felt electrode respectively assembled into all-vanadium redox flow batteries, indicating that the modified electrode shows a smaller polarization effect during the charge-discharge process and at the same time exhibits a higher capacity.

[0035] After testing, at a current density of 200 mA / cm 2 for the all-vanadium redox flow battery assembled with the graphite felt electrode prepared in this example, the voltage efficiency is 75% and the energy efficiency is 72%. Example 2

[0036] A method for chemical etching and synergistic surface modification of a carbon felt electrode, comprising the following steps: S1. Dissolve 1.0 mmol of Co(NO3)2·6H2O and 1.0 mmol of KOH in 20 mL of formamide respectively to obtain solution A and solution B. After mixing, stir for 30 min until completely dissolved to obtain a mixed solution; S2. Transfer the mixed solution to a 100 mL high-pressure reactor lined with polytetrafluoroethylene, put in four pieces of 2×2 cm 2 carbon felt, ultrasonically treat for 30 min, then seal the reactor, and heat and react at 170 °C for 12 h; after the reaction is completed, cool to room temperature, collect the graphite felt, wash it with ethanol and dry it at 80 °C for 12 h to obtain a carbon felt electrode precursor; S3. Place the carbon felt precursor in a tubular furnace, heat it to 900 °C at a heating rate of 5 °C / min in an argon atmosphere and anneal for 2 h, then cool, wash and dry to obtain a carbon felt electrode; S4. Immerse the carbon felt electrode in 3.0 mol / L H2SO4 solution for 6 h, wash and dry it to obtain the final carbon felt electrode.

[0037] To test the electrochemical performance of this electrode, assemble this electrode into a all-vanadium redox flow battery for charge-discharge tests. At a current density of 200 mA / cm 2 the voltage efficiency of the all-vanadium redox flow battery is 73%, and the energy efficiency is 70%. Example 3

[0038] A method for chemical etching and collaborative surface modification of a graphite felt electrode, comprising the following steps: S1. Dissolve 1.0 mmol of Co(NO3)2·6H2O and 1.0 mmol of KOH in 20 mL of formamide respectively to obtain solution A and solution B. After mixing, stir for 30 min until completely dissolved to obtain a mixed solution; S2. Transfer the mixed solution to a 100 mL high-pressure reactor lined with polytetrafluoroethylene, put in four pieces of 2×2 cm 2 graphite felt, ultrasonically treat for 30 min, then seal the reactor, and heat and react at 170 °C for 12 h; after the reaction is completed, cool to room temperature, collect the graphite felt, wash it with ethanol and dry it at 80 °C for 12 h to obtain a graphite felt electrode precursor; S3. Place the graphite felt precursor in a tube furnace, heat it to 1000 °C at a heating rate of 5 °C / min in an argon atmosphere and anneal for 2 h, cool it and then wash and dry it to obtain a graphite felt electrode; S4. Immerse the graphite felt electrode in 3.0 mol / L H2SO4 solution for 6 h, wash and dry it to obtain the final graphite felt electrode.

[0039] To test the electrochemical performance of this electrode, assemble this electrode into a all-vanadium redox flow battery for charge-discharge tests. At a current density of 200 mA / cm 2 the voltage efficiency of the all-vanadium redox flow battery is 72.1%, and the energy efficiency is 69.7%. Example 4

[0040] A method for chemical etching and collaborative surface modification of a graphite felt electrode, comprising the following steps: S1. Dissolve 5.0 mmol of Co(NO3)2·6H2O and 5.0 mmol of KOH in 20 mL of formamide respectively to obtain solution A and solution B. After mixing, stir for 30 min until completely dissolved to obtain a mixed solution; S2. Transfer the mixed solution to a 100 mL high-pressure reactor lined with polytetrafluoroethylene, put in four pieces of 2×2 cm 2The graphite felt was ultrasonically treated for 30 min, then the reaction kettle was sealed, and heated at 170 °C for 12 h. After the reaction was completed, it was cooled to room temperature, the graphite felt was collected, washed with ethanol and dried at 80 °C for 12 h to obtain the graphite felt electrode precursor; S3. The graphite felt precursor was placed in a tubular furnace, heated to 900 °C at a heating rate of 5 °C / min in an argon atmosphere and annealed for 2 h. After cooling, it was washed and dried to obtain the graphite felt electrode; S4. The graphite felt electrode was immersed in a 3.0 mol / L H2SO4 solution for 6 h, washed and dried to obtain the final graphite felt electrode.

[0041] To test the electrochemical performance of the electrode, the electrode was assembled into a battery for charge-discharge testing. At a current density of 200 mA / cm 2 the voltage efficiency of the all-vanadium redox flow battery was 70.1% and the energy efficiency was 65.7%.

[0042] The technical features of the above-described embodiments can be combined arbitrarily. For the sake of brevity of description, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, it should be considered as the scope described in this specification.

[0043] The above-described embodiments merely represent several implementation manners of the present invention, and the description thereof is relatively specific and detailed, but it should not be construed as a limitation on the scope of the invention. It should be noted that for those of ordinary skill in the art, without departing from the concept of the present invention, several modifications and improvements can still be made, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention should be subject to the appended claims.

Claims

1. A preparation method of a carbon-based electrode for a flow battery, characterized in that, It includes the following steps: S1. Dissolve cobalt salt and alkali in polar organic solvents respectively, and mix them evenly to form a precursor solution; S2. Place the carbon-based material in the precursor solution and carry out hydrothermal reaction to obtain a carbon-based electrode precursor; S3. Carry out high-temperature carbonization of the carbon-based electrode precursor under an inert gas atmosphere. After the reaction is completed, cool it to room temperature, and then wash and remove impurities from the product to obtain the carbon-based electrode; Among them, in step S1, the polar organic solvent is at least one of formamide, acetonitrile, and N,N-dimethylformamide; In step S2, the temperature of the hydrothermal reaction is 80-200 °C; In step S3, the carbonization temperature is 400-1200 °C.

2. The preparation method of the carbon-based electrode of the flow battery according to claim 1, wherein, The cobalt salt is at least one of cobalt nitrate, cobalt chloride, cobalt acetate, and cobalt sulfate; and / or, the alkali is at least one of sodium hydroxide and potassium hydroxide.

3. The preparation method of the carbon-based electrode of the flow battery according to claim 1, characterized in that, The carbon-based material includes at least one of graphite felt, carbon cloth, and carbon paper.

4. The preparation method of the carbon-based electrode of the flow battery according to claim 1, wherein: In step S1, in the precursor solution, the molar concentrations of the cobalt salt and the alkali are 0.01-0.1 mol / L respectively.

5. The preparation method of the carbon-based electrode of the flow battery according to claim 1, characterized in that: In step S3, the method of washing and removing impurities is to carry out treatment by pickling and / or water washing; the pickling treatment uses at least one of dilute sulfuric acid, hydrochloric acid, and nitric acid, and the acid concentration is 0.5-3.0 mol / L.

6. The preparation method of the carbon-based electrode of the flow battery according to claim 1, characterized in that The inert gas is one of argon, nitrogen, and helium; the gas flow rate is 50-200 mL / min.

7. The carbon-based electrode obtained by the preparation method according to any one of claims 1-6, wherein the surface of the carbon-based electrode has a micro-nano hierarchical porous structure.

8. A flow battery, characterized in that, It includes the carbon-based electrode according to claim 7.

Citation Information

Patent Citations

  • Carbon-based Prussian blue analogue composite material, preparation method and applications thereof

    CN110540216A

  • Porous electrode for flow battery and preparation method of porous electrode

    CN111785978A

  • Preparation method and application of iron-cobalt-phosphorus-nitrogen doped carbon nanofiber

    CN114232138A

  • Method for modifying defects of carbon cloth electrode of iron-chromium flow battery

    CN116031418A

  • Preparation method and application of porous carbon material

    CN116199205A

Cited By

  • Niobium-based complex derivative electrode and preparation method and application thereof

    CN120581609A

  • Nitrogen / metal / nitrogen composite structure flow battery electrode material and preparation method and application thereof

    CN121687978A